The anti-anxiety/depression effect of a combined complex of casein hydrolysate and γ-aminobutyric acid on C57BL/6 mice - Cai, Lei; Tao, Qian; Li, Wenzhi; Zhu, Xiping; Cui, Chun (Frontiers in Nutrition, 2022)
This study investigated the improvement of the anxiety/depression function by the compound of casein hydrolysate and γ-aminobutyric acid (GABA) (casein hydrolysate: GABA = 4:1; CCHAA) on mice induced by chronic restraint stress-corticosterone injection. Animal experiments revealed that oral administration of CCHAA significantly reversed the anxiety/depression-like behaviors. Compared to the model control group, body weights were increased after treatment with CCHAA groups (1.5, 0.75 mg/(g·d)). As a diagnostic index of anxiety and depression, we assessed GABA and 5-HT levels in response to CCHAA ingestion. The GABA and 5-HT levels were increasingly enhanced by the CCHAA diet. In addition, histopathological changes in the hippocampus CA3 region of the anxious/depressed mice were also alleviated after the treatment with the CCHAA. Thus, the casein hydrolysate and GABA formula diets may induce beneficial effects on the mice with anxiety/depression.